Impact of B‐type natriuretic peptide (BNP) on development of atrial fibrillation in people with Type 2 diabetes. Issue 8 (18th August 2015) - Kishimoto, I.; Makino, H.; Ohata, Y.; Tamanaha, T.; Tochiya, M.; Kusano, K.; Anzai, T.; Toyoda, K.; Yasuda, S.; Minematsu, K.; Ogawa, H.
Abstract: Aims: To examine if a simple biomarker can identify people with diabetes who are at high risk of atrial fibrillation. Methods: A retrospective cohort study was conducted at a single centre in people with Type 2 diabetes referred to our department between January 2000 and December 2007. In 517 consecutive people without any history, signs or symptoms of atrial fibrillation at baseline, the association between baseline B‐type natriuretic peptide level and future atrial fibrillation incidence was examined, with adjustments for other potentially confounding factors. Results: A total of 28 people were diagnosed with new‐onset atrial fibrillation during a median 6‐year follow‐up. When people were categorized into three groups according to B‐type natriuretic peptide clinical thresholds (20 and 100 pg/ml), hazard ratios for the development of atrial fibrillation in the middle and highest B‐type natriuretic peptide groups were 2.8 and 9.4, respectively, compared with the lowest B‐type natriuretic peptide group. Time‐dependent receiver‐operating curve analysis identified a threshold for B‐type natriuretic peptide to detect atrial fibrillation development of 52.8 pg/ml (sensitivity 75.2%, specificity 68.8%). The B‐type natriuretic peptide predictive value was independent of and similar to that of left atrial size and ventricular dimension. Conclusion: In people with Type 2 diabetes, high baseline B‐type natriuretic peptide levels were significantly associated with future atrial fibrillation development. What's new?: Strategies to improve detection of atrial fibrillation are urgently needed in diabetes. We show that, in people with Type 2 diabetes without symptoms, signs or a diagnosis of atrial fibrillation, the high baseline B‐type natriuretic peptide level in plasma is a significant risk marker for development of future atrial fibrillation. The association between B‐type natriuretic peptide and atrial fibrillation was independent of other risk markers or comorbidities. The B‐type natriuretic peptide threshold for detecting future atrial fibrillation development was examined by receiver‐operating curve analysis of survival data. The predictive value of B‐type natriuretic peptide was similar to that of echocardiographic variables.